Beyond Lobbying Expenditures: How Lobbying Breadth and Political Connectedness Affect Firm Outcomes - Ridge, Jason W.; Ingram, Amy; Hill, Aaron D. (Academy of Management Journal, 2017)
The extant lobbying literature largely focuses on the effects of firm aggregate lobbying expenditures, suggesting that more lobbying expenditures fuel positive firm benefits. We argue the focus on aggregate expenditures overlooks how expenditures are targeted and the influence of those targeting the expenditures; as such, exploring such factors will both add insight to our understanding of the theoretical mechanisms underlying lobbying and clarify contradictory findings. Specifically, we argue a successful lobbying strategy consists of both the breadth of government targeted and the political connectedness of the firm. Empirical results support our contentions that lobbying breadth and political connectedness affect the benefits firms receive from lobbying, which we operationalize both using government contracts and firm economic performance. Our analyses imply that more is not always better in the case of lobbying breadth, as the benefits accrued via dispersing lobbying across more governmental entities reaches a point of diminishing returns when lobbying breadth reaches high levels. Further, political connectedness has a moderating effect on the outcomes of lobbying breadth. We conclude the article with a discussion of the theoretical and practical relevance of this research and offer avenues forward for future research.